Pengaruh Literasi Keuangan Terhadap Perilaku Konsumtif Generasi Milenial Di Kota Bandung - Zahra Qurotaa’yun; Astrie Krisnawati (JAF (Journal of Accounting and Finance), 2019)
Consumptive behavior is actions taken to fulfill various types of human needs. If consumption is carried out excessively and not just based on needs, then it is not a reasonable consumption anymore, but it has become a consumptive behavior. Millennials are considered as the most consumptive generation, especially online shopping and prioritizing short-term needs rather than long-term needs. Theoretically consumptive behavior is influenced by low financial literacy. This research was conducted in the millennial generation in Bandung, which in 2019 was 19-38 years old. The sample used in this study was calculated using Slovin formula so that there were at least 400 respondents. Technique used in this research is nonprobability sampling with a purposive sampling approach. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results of this study concluded that financial literacy had a significant negative effect on the consumptive behavior of millennial generation in the city of Bandung. With the level of financial literacy and consumptive behavior included in the medium category.